2022
DOI: 10.1177/00302228211057992
|View full text |Cite
|
Sign up to set email alerts
|

Health Care Providers’ Attitudes Toward Do-Not-Resuscitate Order in COVID-19 Patients: An Ethical Dilemma in Iran

Abstract: This study aimed to investigate the health care providers’ attitudes toward the Do-Not-Resuscitate order (DNR) in COVID-19 patients. This study was conducted on 332 health care providers (HCPs) at the COVID-19 referral hospital in Shahroud, Iran by convenience sampling method. The study tools included a demographic information form and the DNR attitude questionnaire. Significance level was considered 0.05 for all tests. The mean scores of attitudes toward DNR order, the procedure of DNR, some aspects of passiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 27 publications
(28 reference statements)
0
2
0
Order By: Relevance
“…Nurses can especially be helpful to patients in this difficult decision-making process [185,186], and having DNR orders can influence the aggressiveness of nursing care attitudes [187]. Regarding the COVID-19 pandemic, one study in Iran found that healthcare providers' attitude towards DNR implementation in patients with COVID-19 was positive despite a legal ban on DNR implementation in Iran [188].…”
Section: Values What Is Each Team Member's Own Values Towards End-of-...mentioning
confidence: 99%
“…Nurses can especially be helpful to patients in this difficult decision-making process [185,186], and having DNR orders can influence the aggressiveness of nursing care attitudes [187]. Regarding the COVID-19 pandemic, one study in Iran found that healthcare providers' attitude towards DNR implementation in patients with COVID-19 was positive despite a legal ban on DNR implementation in Iran [188].…”
Section: Values What Is Each Team Member's Own Values Towards End-of-...mentioning
confidence: 99%
“…During the COVID-19 pandemic, increased patient admissions and staff risk performing CPR without adequate personal protective equipment contributed to public concern that clinicians would make unilateral decisions to not offer CPR against patient preferences (14–16). There was also concern that use of UDNR orders may exacerbate racial and ethnic disparities in patient outcomes already existing during the pandemic (17, 18).…”
mentioning
confidence: 99%